Body and society. Sociology of the body in research and theoretical concepts - Byczkowska-Owczarek, Dominika (2023)
The book presents issues of the sociology of the body in relation to various spheres of social life in which processes, values, norms and other social phenomena influence the human body. The book presents the assumptions and most important classical and contemporary sociological theories in relation to the human body. It contains twelve chapters covering various substantive areas of the sociology of the body such as work, sport, beauty, media, gender, sexuality, food and eating, medicine, disease and disability, time and religion. Each chapter presents: the most important theoretical concepts relating to the discussed topic, the achievements of scholars in particular area of the sociology of the body, the most important studies, including classic ones and key concepts."Body and society. Sociology of the Body in Research and Theoretical Concepts” is a book addressed to sociologists of various specialties who want to expand their knowledge of the sociology of the body or supplement information on the role of corporeality in such areas as sports, work, religion or media. It was prepared by specialists in the field as part of the work of The Sociology of the Body Section of the Polish Sociological Association.
Keywords: sociology of the body; sociology in Poland; the human body